Pengembangan Aplikasi Android MVTE dengan Metode RAD - Fikri Amrullah; Mardiana Andarwati; Galandaru Swalaganata; Hudan Eka Rosyadi (Universitas Merdeka Malang, 2021)
Deaf students discuss activities with other students, Deaf students need tools in participating in discussion activities, whereas so far, Deaf students have only relied on the ability to read the lips of their interlocutors. This research produces an assistive or assistive technology, namely the Android-based MVTe (Mobile Voice To Text) application where this application simply changes the voice in written form. This application was developed using the RAD (Rapid Application Development) method. The RAD method speeds up the work process due to its compact working process. The application trial was carried out on an IT expert, 5 deaf students, and 5 lecturers in the Information Technology Faculty, Universitas Merdeka Malang. The average test result is 81.3% with a feasible category for use.